Technological tools for virtual teaching and their effect on the satisfaction of online learning - Chamorro-Atalaya, Omar; Alvarado-Bravo, Nestor; Aldana-Trejo, Florcita; Huarcaya-Godoy, Madison; Anton-De los Santos, Marco; Anton-De los Santos, Juan; Fierro-Bravo, Maritte (Institute of Advanced Engineering and Science, 2022)
The objective of the research is to analyze the satisfaction of the online learning of the applied electricity subject, when implementing technological tools for virtual teaching. The development of the research determines a high level of student satisfaction, finding the perception of reliability with 93.05%, that of security with 93.2%, that of answer’s capacity with 90.73% and empathy with 82.87%. Satisfaction with the technological tools of virtual teaching is related to the adequate and accessible use of simulation software during online learning, which allowed compliance with the syllable. In addition to the security and confidence when the teacher is willing to help him in the use of the simulation software, responding to it appropriately and quickly. Satisfaction of online learning of the applied electricity subject using virtual teaching tools is related to the teacher's sample of concern towards students regarding their academic needs and their expressed interests.